Study of social representations on Aids in professionals of health who act in the context of the soropositividade for the HIV - Ribeiro, Cristiane G.; Coutinho, Maria da Penha L.; Saldanha, Ana Alayde W. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: the aids is a phenomenon whose consequences happen in the community as a problem politician, economic and psicossocial, exertingeffect on the population in general and the professionals of health particularly, being able to intervene with the quality of the attendance. Objective: this research objectified to identify to the Social Representations of the aids of doctors and nurses who take care of soropositivos patients for the HIV,aiming at to contribute for the perfectioning of the practical ones of these professionals and, consequently, in the effectiveness of the treatment. Methods:the sample was composed for 56 professionals of health who act directly in the context of the aids, the Services of Public Health of João Pessoa-PB, composed, in its majority, for professionals of the feminine sex (82%), with superior age the 44 years (48%). The data had been collectedby the technique of free association of words, processed through Tri-Deux-Mots software and interpreted by means of the factorial analysis of corres-pondence (AFC). Results:the professionals build representations of the aids as one badly terrible one but that she can be minimized, depending onthe emotional, cultural and economic conditions of the patient, associate to a general idea on that the development of the illness depends on the formas the patient chore with it and of the support that receives from the family. Conclusion:these results express that the social representations on theaids and its treatment, for these professionals structuralize in the interface of the complexity, placing in game scientific and profane knowledge, aswell as social and contextual values. Being thus, she is necessary to articulate, in the analyses, the medical conceptions and the implications of thesocial conceptions that make them echo.